Genetic Determinants of Myocardial Infarction Risk in Familial Hypercholesterolemia - Zhao, Pei Jun (CJC Open, 2019)
BACKGROUND: Familial hypercholesterolemia (FH) is an inherited condition of elevated serum low-density lipoprotein (LDL) cholesterol leading to premature coronary heart disease. We evaluated whether FH mutations are independently associated with the development of myocardial infarction (MI), after adjusting for LDL cholesterol level and clinical risk factors. METHODS: In 182 unrelated patients from different families referred with clinically suspected FH, targeted next-generation DNA sequencing was performed on 73 lipid-related genes and 178 single nucleotide polymorphisms, at 300-times mean read depth, to identify monogenic mutations and high-risk single nucleotide polymorphisms. RESULTS: Pathogenic FH mutations were identified in 27% of patients. Patients with mutations, compared with those without, were 12 years younger when referred to the lipid clinic (P < 0.001) and had higher baseline and post-treatment LDL cholesterol by 1.11 mmol/L (P < 0.001) and 0.62 mmol/L (P = 0.01), respectively. The hazard ratio for premature MI with respect to having an FH mutation, controlling for sex, hypertension, body mass index, diabetes, LDL cholesterol, and smoking, was 4.51 (P = 0.002). CONCLUSION: FH is a genetically diverse condition. FH mutations are independently associated with higher risk of premature MI in patients referred for hypercholesterolemia. Therefore, genotyping could guide cardiovascular risk stratification in the personalized treatment of FH.